Infection control implications of the laundering of ambulance staff uniforms and reusable mops. Issue 1 (May 2017) - Mackay, W.G.; Whitehead, S.; Purdue, N.; Smith, M.; Redhead, N.; Williams, C.; Wilson, S.
Summary: There is a lack of published studies on laundering in ambulance services. We performed bacterial culture on soiled and unsoiled uniforms and reusable mop heads artificially contaminated with Escherichia coli, Staphylococcus aureus, and Clostridium difficile spores. Current laundering processes used for routine cleans in the ambulances appears, from our simulations, to be effective at reducing vegetative pathogenic bacteria to undetectable levels, <3.398 log10 colony-forming units ( S. aureus and E. coli ). Reduced levels of C. difficile were still detected after laundering but the risk this poses for infection is unknown, as background levels of these spores in the environment are unknown.